Germani und invento nomine (Tac. Germ. 2, 3) - Tscherniak, Alexander (Hyperboreus, 2016)
Tacitus’s attempt (Germ. 2, 3) to represent the left shore Germans as the source of the spreading of the ethnic name Germani upon all Germany appears to the author of the paper unconvincing. Tacitus speaks about transgression of Rhein by the German union of tribes Tungri, who were probably summoned by the Treveri to help them in their struggle with the Aeduaci, the descendants of Cimbri and Teutones. Later Celts came to name Germani all German-speaking mercenaries from the right shore of Rhein. Caesar was the ﬁrst who started using Germani as an ethnic name. Tacitus tried to maintain this usage, asserting that Germani is an original name of one of the tribes settled in Gaul, which gradually became the designation of Germans by Gauls, and later even the self-designation of Germans. The last of these statements is false, and the ﬁrst is dubious. Tacitus’ source however was probably aware that Germani was an old war-cry.